Increasing Children's Religious Behavior Through the Tahfidzul Qur'an Program in Matur Sub-District - Fadhilah Hanun, Salma (BiCED Proceeding, 2024)
This research was motivated by several problems that the author found where before participating in the Qur'an tahfidz program, children in the jorong sidang tangah, matur sub-district had behavior that could be said to be not good such as often resisting or arguing with parents. Because during this time with the development of the times many of today's children are disrespectful to their parents, do not have good ethics to parents, then those who initially fill their days with things that are not useful such as playing games with their friends until they forget the time, and often neglect to do the five daily prayers. But after the children in the jorong sidang tangah matur sub-district joined the tahfidz Tahfidz Qur'an Syifaul Qalbi program, their behavior began to change into better behavior than before. The type of research that the author uses in this research is qualitative research methods. The data collection techniques I will use are based on interviews, documentation and my own observations. Interviews were conducted by in-depth interviews with teachers at Tahfidz Qur'an Syifaul Qalbi.